Does nest site availability limit the density of hole nesting birds in small woodland patches? - Loman, Jon (Web Ecology, 2006)
By providing nest boxes, previous studies have shown that nest sites are in short supply and limit the populations of several small passerines, including the Great Tit Parus major, the Blue Tit P. caeruleus, and the Pied Flycatcher Ficedula hypoleuca. Can this influence their distribution over a range of small woodland patch sizes in a heterogeneous landscape? To investigate this, a study was conducted in a heterogeneous agricultural landscape, with a mixture of wooded patches and cropped fields, in southern Sweden. The descriptive part of the study involved mapping territories of the three species in 135 patches. These species avoided small (< 1 ha, Pied Flycatcher) or very small (< 0.2 ha, the two tit species) forest patches in this landscape. In an experimental part, a subset of 34 patches, 0.01 to 24 ha in size was used. Territories were mapped in a first yr as a control. In a second yr, patches were matched by size and vegetation and nest-boxes were provided in one patch of each pair. Territories were again mapped. Providing nestboxes increased the density of breeding Great Tits in patches of all sizes and expanded their use of very small patches. The nest-boxes increased the density of Pied Flycatchers in large patches but not in small patches. So, is the lack of territories in small patches due to shortage of nest sites? The outcome of the experiment suggests nest site limitation as a cause of the observed Great Tit discrimination against very small habitat patches. The lack of Pied Flycatchers in small patches must however have another basis than lack of nest sites. The effect of providing nest-boxes on Blue Tit distribution was inconclusive.